Loss of the normal N-ras allele in a mouse thymic lymphoma induced by a chemical carcinogen. - Guerrero, I (1985)
Young mice injected with the carcinogen N-nitroso-N-methylurea develop thymic lymphomas 2-4 months later. We previously have shown that these tumors frequently contain an activated N-ras gene that can transform rodent fibroblasts in vitro. We report here the intron/exon structure of such an activated N-ras gene and the sequence of its four coding exons. A single nucleotide change is responsible for the transforming alteration, a C----A transversion in the first base of codon 61. Through the use of synthetic oligonucleotides as hybridization probes, we show that this tumor lacks the normal allele of the N-ras gene. The implications of this finding for oncogene dominance are discussed.